Human microRNA hsa-miR-15b-5p targets the RNA template component of the RNA-dependent RNA polymerase structure in severe acute respiratory syndrome coronavirus 2. (3rd August 2021) - Sato, Akira; Ogino, Yoko; Tanuma, Sei-ichi; Uchiumi, Fumiaki
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a pandemic of the coronavirus disease in 2019. RNA-dependent RNA polymerase (RdRp) plays an essential role in RNA replication and transcription in SARS-CoV-2. In this study, we focused on the RNA template component of viral RdRp structure and analyzed human microRNAs (miRNAs) targeting specific sequences in this RNA. By examining miRNA databases and using an in vitro RNA-RNA interaction assay, we observed hsa-miR-15b-5p interacting with the RNA component of viral RdRp. Our findings provide evidence that hsa-miR15b-5p may suppresses viral infection and proliferation by targeting the RNA template component of SARS-CoV-2 RdRp.